Strategies and guidelines for urban sustainability: the impacts of the Covid-19 on energy systems - Gaglione, Federica (TeMA - Journal of Land Use, Mobility and Environment, 2021)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is a continuous update about emerging topics concerning relationships among urban planning, mobility and environment thanks to a collection of short scientific papers written by young researchers. The Review Notes are made up of five parts. Each section examines a specific aspect of the broader information storage within the main interests of the TeMA Journal. In particular: The Town Planning International Rules and Legislation Overview section aims at presenting the latest updates in the territorial and urban legislative sphere. The Covid-19 pandemic is causing a major impact on energy systems. Improving the energy efficiency of urban areas is now the cornerstone of scientific community and the European Commission discussions. Thus, the content of this review note aims at carrying out an analysis of the latest documents of the European Commission before and during the slow recovery from Covid-19 with the aim of identifying the priorities and areas on which to intervene to reduce energy consumption in different territorial contexts.